Um rio confluente de memórias: narrativas de professoras sobre a história da educação de crianças no Acampamento CHESF (1949-1985) - Lima, Laíse Soares (2022)
The purpose of this thesis is to understand from the memory of the school routine of teachers who worked in the schools of Acampamento Chesf in the period from 1949 to 1985, how the educational process occurred with the children. Based on the premise that the school routine establishes concepts of subjects and social practices for the education of children, we specifically seek to: identify the ordering of plans and actions undertaken by teachers; recognize the objectives of educational institutions for children; explain the movement of relations between children and teachers; and enunciate the political, cultural, and social interference immersed in children's experiences. The time frame between the years of 1949 to 1985 corresponds, respectively, to the start of operations of the company CHESF in the city of Paulo Afonso, BA, Brazil, with the beginning of the construction of educational institutions within the camp, and to the period of completion of the hydroelectric construction works, which comprises the social unification of the camp with the other part of the city, named Vila Poty. The study is classified in the field of Social History of Childhood and in the History of Education, guided by the concepts of childhood from Modernity and the contributions of the educational concepts of Historical-Critical Pedagogy. Based on the methodological approach of Oral History, we used as sources, in particular, the memories of twelve teachers who worked in the Company's schools with children aged between four and fourteen, who were part of the kindergarten and primary school classes, and, in addition, photographs; normative documents, such as decrees and reports. The narratives were divided into four categories of analysis that approach the teachers' profile; the pedagogical organization of the schools; the teaching proposition for children; and the interference that the Company and the community both emitted over the educational institutions. The results show that the teachers were all women from the perspective that the female representation would be fundamental for a humanist formation, based on care and free from conflicts. The teaching practice was based on an educational project with common goals for all schools, regardless of the economic status of their children, systematized by the company's directors in partnership with the directors of the educational institutions and carried out through weekly plans, which were supervised by the pedagogical coordination. The teaching plan included cultural, historical, scientific, and social contents for an integral education, aiming at an ideal of a Chesfian worker, configured by a civilizing bias, with all the necessary requirements to continue the company's work and values. Didactic and cultural activities were mediated by norms and supervisions, which did not hinder affections and positive relationships between the subjects, who were in the internal and external environments of the school, sharing feelings, consolidated over the years, and prevailing in the meetings and in the memory.